(untitled) (Jurnal Ekonomi dan Manajemen, 2025)
The rapid advancement of technology and information, particularly in online complaint services, has significantly progressed. This development demands that employees enhance their skills to keep up with technological advancements. Human resource (HR) competency development programs are designed to maximize the achievement of organizational goals. In addition to competency improvement, there is also a demand for the implementation of e-government practices, which are currently underway while considering government performance aspects, as reflected on the website ppid.mojokertokab.go.id. This study aims to analyze the influence of e-government and competency on government performance and the quality of public services on the website www.ppid.mojokertokab.go.id. The research population consists of 62 website visitors, including those who have submitted complaints, with the sample selected using a saturated sampling technique. Data collection was conducted through questionnaires and analyzed using SPSS Version 22 and path analysis methods. The results indicate that: 1) e-government significantly influences government performance, 2) competency significantly influences government performance, 3) e-government significantly influences the quality of public services, 4) competency significantly influences the quality of public services, 5) government performance significantly influences the quality of public services, 6) e-government indirectly influences the quality of public services through government performance, and 7) competency indirectly influences the quality of public services through government performance.